The Effect of Perceived Usefulness, Perceived Ease of Use, Perceived Security, and Cashback Promotion on Behavioral Intention to the DANA E-Wallet - Raninda, Ratna (Jurnal Ilmiah Manajemen Kesatuan, 2022)
Changing patterns of behavior in public financial transactions during this pandemic has increased the use of e-wallet services. One of the Indonesian people's most widely used e-wallet services is DANA. This study aims to determine the effect of perceived usefulness, perceived ease of use, perceived security, and cashback promotion on behavioral intention to the DANA e-wallet (a survey of people in the Special Region of Yogyakarta). The sampling technique used is non-probability sampling with the purposive sampling method. The number of samples in this study was 100 respondents with the criteria of people who have a DANA account but have never used it for transactions. The analytical technique used is multiple linear regression analysis. Based on the results of this study, it was found that perceived usefulness, perceived ease of use, perceived security, and cashback promotion simultaneously or together had an effect on behavioral intention in DANA e-wallet with a significance value of 0.00 < 0.05 and an Adjusted R-value by 55.1%. This shows that the variables perceived usefulness, perceived ease of use, perceived security, and cashback promotion can explain 55.1% of behavioral intention variables, and the remaining 44.9% is influenced by other variables outside of this study. In addition, this study also obtained results that perceived usefulness, perceived ease of use, perceived security, and cashback promotion partially or one by one affect behavioral intention.